2018
DOI: 10.1094/pdis-02-17-0199-re
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Powdery Mildew Resistance Gene in Wheat Breeding Line 10V-2 and Its Application in Marker-Assisted Selection

Abstract: Powdery mildew, caused by Blumeria graminis f. sp. tritici, is a serious disease of wheat (Triticum aestivum L.) throughout the world. Host resistance is the most effective and preferred means for managing this disease. Line 10V-2, a wheat breeding line with superior agronomic performance, shows broad-spectrum seedling resistance to powdery mildew. Genetic analysis demonstrated that its resistance was controlled by a single dominant gene, tentatively designated Pm10V-2. This gene was localized near the documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Although this locus has been cloned by mutant chromosome sequencing (Sánchez-Martín et al, 2016) and analysis of the annotated genes in the mapping interval using the reference genome of Chinese Spring , no transgenic evidence was provided to confirm that the cloned sequence is the unique functional element conferring resistance to powdery mildew. Additionally, other reports showed that all the homologous sequences in different Pm2 allele donors have the exactly the same sequence, yet these Pm2 alleles exhibit significantly different resistance spectra that cannot be explained by the background differences of the resistant germplasms (Jin et al, 2018;Ma et al, 2018). In this study, the marker order across the PmJM23 interval showed inversion and recombination phenomena (Figure 2 and Table 3).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Although this locus has been cloned by mutant chromosome sequencing (Sánchez-Martín et al, 2016) and analysis of the annotated genes in the mapping interval using the reference genome of Chinese Spring , no transgenic evidence was provided to confirm that the cloned sequence is the unique functional element conferring resistance to powdery mildew. Additionally, other reports showed that all the homologous sequences in different Pm2 allele donors have the exactly the same sequence, yet these Pm2 alleles exhibit significantly different resistance spectra that cannot be explained by the background differences of the resistant germplasms (Jin et al, 2018;Ma et al, 2018). In this study, the marker order across the PmJM23 interval showed inversion and recombination phenomena (Figure 2 and Table 3).…”
Section: Discussionsupporting
confidence: 52%
“…This suggests that Jimai 23 is an elite resource for resistance breeding. Frontiers in Genetics | www.frontiersin.org markers Icssl326 and Icssl795, and when inoculated with isolate YT01 that was avirulent to both Jimai 23 and Liangxing 99 (Pm52), we detected Pm2-linked marker polymorphisms using five Pm2-linked markers (Cfd81, Swgi069, Bwm20, Bwm21, and Bwm25; Ma et al, 2018) and no Pm52-linked marker polymorphism using Pm52-linked markers Icssl326 and Icssl795 in Jimai 23 × Tainong 18 population. By combining the genealogical relationship between Jimai 22 and 23 with the marker detection results, we confirmed that Jimai 23 has a Pm gene nearby or in the Pm2 interval, which we tentatively designate as PmJM23.…”
Section: Evaluation Of Powdery Mildew Resistance In Jimai 23mentioning
confidence: 96%
See 1 more Smart Citation
“…The PCR procedure was as follow: 94°C for 5 min, followed by 36 cycles of 94°C for 30 s, 58°C for 30 s, 72°C for 40 s, and a final extension at 72°C for 10 min. The PCR products were separated in 8% non-denaturing polyacrylamide gels with 29:1 ratio of acrylamide and bis-acrylamide, and silver-stained prior to visualizing the banding patterns [68].…”
Section: Development and Verification Of Rye Specific Pcr-based Markersmentioning
confidence: 99%
“…Simple sequence repeats (SSRs), also known as microsatellites or short tandem repeats (STRs), consist of 2 to 6 base-pair motifs repeated several times in tandem. As a consequence of their wide distribution and high mutation rate in eukaryotic genomes [ 1 ], SSRs have been used in genetic diversity and population structure studies [ 2 , 3 , 4 , 5 ], for discrimination among species or breeds [ 6 , 7 ], in marker-assisted selection [ 8 , 9 , 10 ] and in evolution analysis [ 11 ]. In humans, SSRs were predicted to be bound by protein-coding transcripts, long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) and affect competing endogenous RNA crosstalk [ 12 ].…”
Section: Introductionmentioning
confidence: 99%